Outcome of cardiac sarcoidosis after radiofrequency ablation and placement of AICD- A propensity matched analysis - Bandyopadhyay, Debabrata; Sahoo, Debasis; Zein, Joe; Brunken, Richard C; Tchou, Patrick J; Culver, Daniel A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Cardiac Sarcoidosis (CS) can lead to life-threatening ventricular dysrhythmias and sudden death. Immunosuppressive medications, radiofrequency ablation (RFA), and implantable cardioverter defibrillators (ICD) have been utilized to manage ventricular dysrhythmias but their benefits remain poorly defined. Objective: The aim of this study is to assess the durability of RFA in CS population and to determine outcome predictors after RFA. Methods: We compared the CS patients who had RFA±ICD against those with only ICD placement and contemporaneous patients with arrhythmogenic right ventricular dysplasia (ARVD) who had RFA. We analyzed time to a composite first event of appropriate ICD therapy, subsequent RFA, cardiac transplantation or death. We also evaluated variables predicting recurrence of ventricular dysrhythmias, including LVEF, cardiac involvement on PET scan, percent of ventricular ectopic beats, number of inducible VT foci and success of the RFA procedure. We used propensity matching and multivariable regression to adjust for baseline differences between the groups to identify outcome predictors. Results: Thirty ablations for VT were performed in 20 CS patients (13 had concomitant ICD placement); 12 ablations were done in eight ARVD patients and 33 CS patients with only ICD placements were included in this cohort. The median follow-up period was 48 (9-173) months. Fourteen (70%) patients reached composite end points after RFA compared to 13 (63%) following ICD placement and five (87%) in the ARVD cohort. There was a significant time difference to reach composite end points (p=0.02) in favor of ICD only cohort. The median number of ICD therapies were higher in the CS-RFA group (p=0.01). The requirement for ICD therapy increased over time following RFA, especially after 12 months. Variables predicting earlier time-to-event were EF <40% (OR=13.2) and unsuccessful RFA procedure (OR=7.9). The presence of more than one inducible VT morphology was associated with higher likelihood of unsuccessful RFA (p=0.03). Conclusion: RFA can be an effective modality for the short-term treatment of ventricular dysrhythmias in cardiac sarcoidosis; however, after more than 12 months, the number of appropriate therapies escalates. Accordingly, ICD placement is recommended for all patients who undergo RFA for VT associated with CS, whether it is successful or not. Low LVEF and unsuccessful ablation were strong predictors of future events.